Eksplorasi Potensi Tanaman Lokal dan Pengaruh Formula Mordant sebagai Upaya Diversifikasi Motif Ecoprint - Mudjiati, Mudjiati; Suryani, Leny (IAI Nasional Laa Roiba Bogor, 2024)
This research explores the potential of local plants as materials in ecoprint techniques to create motif differentiation in fashion products. The study also aims to discover the optimal formula in the mordanting process. This research employs a practice-based research method to explore the potential of local plants as ecoprint materials and analyze the mordant formula for motif differentiation. The results come from the use of various types of leaves in ecoprint techniques to produce unique patterns and colors on fabric. Each leaf, such as guava, teak, mahogany, henna, and acacia, imparts different color characteristics and patterns. The formulation of the mordant solution and the technique of soaking the fabric have been shown to affect the ecoprint results, with alum mordant yielding darker and more defined colors, while potassium aluminum sulfate produces lighter colors.